THE DEVELOPMENT OF INNOVATIVE TECHNOLOGIES OF NON-FINANCIAL SERVICE IN THE SPHERE OF BANKING SERVICES - Kulikov, Nikolai; Kudrjavceva, Julija (Revista Inclusiones, 2020)
The paper deals with the development of non-financial service in the sphere of banking services and the formation of new segments in the customer service market. It reveals significant changes in the image of banks and the way they work due to innovative technologies. It investigates the appearance of client-centered innovative services, which enlarge the range of provided products and non-financial services including electronic documentary calculations, etc.